Dampak trauma masa kecil terhadap perubahan struktur otak dan manifestasi klinis Gangguan Stres Pasca-Trauma (PTSD) - zahra, arwa fathimatuz (Maliki Interdisciplinary Journal, 2026)
Based on a systematic search of scientific literature in articles, journals, and books, several changes in brain structure and PTSD were found to be caused by childhood trauma. Post-traumatic stress disorder (PTSD) is a mental health condition that can develop after experiencing or witnessing a traumatic event, such as combat or sexual abuse. Individuals with PTSD often struggle to cope with the traumatic experience, which is triggered by factors unique to each person, causing symptoms such as anxiety, panic attacks, and flashbacks. Areas such as the hippocampus, amygdala, and prefrontal cortex are thought to be affected by PTSD. The purpose of this review is to analyze how trauma, particularly childhood trauma, affects the brain’s neuroanatomy and gives rise to the clinical manifestations of PTSD. The study results indicate that PTSD comprises two constructs: neurological hypersensitivity and psychological hypersensitivity. Based on these constructs, it can be understood that PTSD is related to the brain’s neurobiological systems. Possible trearment steps include reducing emotional responses, encouraging recollection and “coming to terms” with the event, developing more effective coping strategies, and addressing residual issues.